Long‐Term, High‐Resolution Permafrost Monitoring Reveals Coupled Energy Balance and Hydrogeologic Controls on Talik Dynamics Near Umiujaq (Nunavik, Québec, Canada) - Philippe Fortier; Nathan L. Young; Jean‐Michel Lemieux; Michelle A. Walvoord; Richard Fortier (Water Resources Research)
Abstract Rising temperatures in the Arctic and subarctic are driving the rapid thaw of permafrost by reducing permafrost cooling, increasing active layer thickness, and promoting talik formation. In this study, the cyrohydrogeology of a permafrost mound located within the discontinuous permafrost zone near Umiujaq (Nunavik, Québec, Canada) is characterized through the analysis of a dataset covering more than two decades of monitoring. This dataset captures a high degree of interannual variability in air temperature and ground thermal conditions, as well as the dynamics of a supra‐permafrost talik. Data indicate that variable saturation and advective heat transport directly contribute to the expansion and contraction of the talik. Data further indicate the presence of two distinct thermo‐hydrologic settings resulting from differences in surface conditions, as well as subsurface thermal and flow regimes. The first, found at the top of the mound feature, is characterized by very low moisture contents (<0.05 m3/m3), while the second, found at the side of the mound feature, shows higher annual moisture contents that strongly influence the dynamics of heat and groundwater flow. The data were synthesized into a detailed conceptual model of the cyrohydrogeological dynamics that highlights the important role of hydrogeological characterization and long‐term data sets in understanding the effects of groundwater flow on seasonal frost and permafrost dynamics. Specifically, the results presented here show that in the absence of long‐term data sets, longer‐period transient phenomena such as talik expansion and contraction may be misrepresented as uni‐directional feedback loops, as opposed to highly dynamic temporary phenomena.